Afinidades eletivas: A funarte e o samba carioca como patrimônio da cultura nacional - Da Costa Garcia, Tânia [UNESP] (Universidade do Estado de Santa Catarina, 2017)
This article maps and analyze the vast network of sociability composed of journalists, musicians and producers involved with popular music that, in the second half of the 20th century, occupying places of power in the written press, radio stations, and in public institutions, managed, in the years of 1970 and 1980, to monumentalize artists and repertoires of the musical universe of Rio de Janeiro as heritage of the national culture. It focus on two projects developed in the Department of Popular Music of the National Art Foundation: Lúcio Rangel, contest of monographies, and Almirante, edition of discs.
Elective affinities: The funarte and the samba as heritage of national culture
Keywords: Cultural heritage; Funarte; Network of sociability; Popular music; Samba